User Sentiment Analysis X Towards Makan Bergizi Gratis Program Using Automatic Labeling Technique with Deepseek AI - Julianto, Indri Tri; Nurpajar, Dini Siti (Journal of Intelligent Systems Technology and Informatics, 2025)
Public perception of national nutrition initiatives is instrumental in shaping inclusive and data-driven policy development. In Indonesia, the "Makan Bergizi Gratis" (MBG) program introduced by President Prabowo has drawn significant attention, particularly on the X platform (formerly Twitter). This research topic was selected due to its national urgency and political significance, as the MBG program emerged as a key agenda during the 2024–2025 political transition. Therefore, examining public sentiment is essential to assess policy acceptance and identify areas for improvement. This study analyzes user sentiment toward the MBG policy using an automatic labeling approach supported by DeepSeek AI and the VADER Lexicon, followed by sentiment classification through the K-Nearest Neighbor (KNN) algorithm. The research involved five main stages: collecting 1,704 tweets from X between January 2024 and March 2025, preprocessing the text, conducting automatic sentiment labeling, applying TF-IDF for vectorization, handling class imbalance using the Synthetic Minority Over-sampling Technique (SMOTE), and classifying sentiments using KNN. The results indicate that without SMOTE, the VADER model achieved higher accuracy (93.49%) but lower Cohen's Kappa (0.16), while DeepSeek AI yielded lower accuracy (73.67%) but slightly higher Kappa (0.17). After SMOTE was applied, accuracy declined (VADER to 77.25%, DeepSeek AI to 64.72%), but Kappa scores improved significantly (VADER to 0.65, DeepSeek AI to 0.47), indicating more balanced and consistent sentiment predictions across classes. In conclusion, integrating automatic labeling, SMOTE, and KNN provides a reliable and scalable framework for analyzing large-scale sentiment on social media platforms, particularly in contexts with imbalanced opinion distributions.